School-based research a guide for education students - Wilson, Elaine (Elaine Geraldine) (SAGE, 2017)
Focused on the needs of the new classroom researcher, and those studying education on Masters-level courses, this is a thorough and thoughtful guide to the research process, covering qualitative, quantitative and mixed research methods.